Injectable hydrogel mediated delivery of gene-engineered adipose-derived stem cells for enhanced osteoarthritis treatment. (21st October 2021) - Yu, Wei; Hu, Bin; Boakye-Yiadom, Kofi Oti; Ho, William; Chen, Qijing; Xu, Xiaoyang; Zhang, Xue-Qing
Abstract : The intra-articular injection of the ECM-mimicking hydrogel loaded with gene-engineered ADSCs that overexpress TGF-β1 shows a synergistic effect on improving the therapeutic outcomes of OA. Abstract : Osteoarthritis (OA), a chronic and degenerative joint disease, remains a challenge in treatment due to the lack of disease-modifying therapies. As a promising therapeutic agent, adipose-derived stem cells (ADSCs) have an effective anti-inflammatory and chondroprotective paracrine effect that can be enhanced by genetic modification. Unfortunately, direct cell delivery without matrix support often results in poor viability of therapeutic cells. Herein, a hydrogel implant approach that enabled intra-articular delivery of gene-engineered ADSCs was developed for improved therapeutic outcomes in a surgically induced rat OA model. An injectable extracellular matrix (ECM)-mimicking hydrogel was prepared as the carrier for cell delivery, providing a favorable microenvironment for ADSC spreading and proliferation. The ECM-mimicking hydrogel could reduce cell death during and post injection. Additionally, ADSCs were genetically modified to overexpress transforming growth factor-β1 (TGF-β1), one of the paracrine factors that exert an anti-inflammatory and pro-anabolic effect. The gene-engineered ADSCs overexpressing TGF-β1 (T-ADSCs) had an enhanced paracrine effect on OA-like chondrocytes, which effectively decreased the expression of tumor necrosis factor-alpha and increased the expression of collagen II and aggrecan. In a surgically induced rat OA model, intra-articular injection of the T-ADSC-loaded hydrogel markedly reduced cartilage degeneration, joint inflammation, and the loss of the subchondral bone. Taken together, this study provides a potential biomaterial strategy for enhanced OA treatment by delivering the gene-engineered ADSCs within an ECM-mimicking hydrogel.